Alpinia galanga Extract Inhibits MCF-7/HER2+ Cells by Inducing Apoptosis - Ibrahim, Sugeng (Universitas Negeri Semarang, 2022)
Background: Cancer is a disease caused by abnormal growth of body tissue cells. Cancer treatment strategy by induce apoptosis and inhibit proliferation. Aim: This research aims to examine the anticancer effect of Alpinia galanga extract on MCF-7/HER2+ breast cancer cells. Method: The MTT Assay cytotoxic test was carried out to determine the growth inhibitory activity. Apoptotic assay to determine the activity of compounds in apoptosis, as well as through a structural approach utilizing various virtual platforms to monitor its activity. Result: Based on the MTT assay Alpinia galanga extract possessed cytotoxic effect in dose-dependent manner with IC50 value of 330.79 μg/mL. The extract induces apoptosis of MCF-7 cells up to 25.56%. Conclusion: It can be concluded that Alpinia galanga extract demonstrated cytotoxic activity toward MCF-7/HER2+ breast through apoptosis induction. This extract had an opportunity to be developed as a potential anticancer agent to overcome breast cancer diseases.